The Nexus Between Environmental, Climate Change, and Social Impact Assessments in Upholding Environmental Rights in South Africa - Marjone Van der Bank; Nicolene Van Rooyen (Constitutionale, 2025)
Section 24 of the Constitution of the Republic of South Africa, 108 of 1996, guarantees environmental rights and promotes sustainable development, yet these rights are not absolute and environmental harm and related human rights violations persist. This article examines the role and interrelationship of environmental impact assessments, climate change impact assessments, and social impact assessments in addressing regulatory gaps and advancing sustainable development. Using a doctrinal and contextual legal approach, it analyses primary sources, including the Constitution, the National Environmental Management Act 107 of 1998 and its regulations, and key case law, notably Earthlife Africa Johannesburg v Minister of Environmental Affairs and Others and Trustees of the Groundwork Trust v Acting Director-General: Department of Water and Sanitation, together with relevant secondary literature. It argues that these three forms of impact assessment operate in a triangulated and interdependent manner, applied at different stages of project development, and collectively contribute to the realisation of section 24 for the benefit of present and future generations.